PROFIL KASUS KULIT DI PUSKESMAS TENGGILIS PERIODE JANUARI-APRIL 2024 - Al Abdul, Teo (Fakultas Kedokteran, Universitas Hang Tuah, 2024)
Objective: To provide an overview of the profile of skin disease cases at the Tenggilis Health Center for the period January-April 2024. Methods: This study is a quantitative descriptive study using medical record data from all patients with skin diseases who underwent treatment at the Tenggilis Health Center for the period January-April 2024. Results: Based on research conducted at the Tenggilis Health Center in the period January-April 2024, 568 patients were obtained with a gender distribution of 233 male patients (41%) and 335 female patients (59%), the distribution of the largest age category was 15- 44 years with 189 cases (33%), the distribution of the largest skin disease category was dermatitis with 302 cases (53%). Conclusion: Based on research conducted at the Tenggilis Health Center for the period January-April 2024, it was found that skin diseases most often occur in women. While 15-44 years old is the largest age category for skin diseases. Dermatitis is the most common skin disease.